Oxytocin Levels Increase and Anxiety Decreases in Mothers Who Sing and Talk to Their Premature Infants during a Painful Procedure - Manuela Filippa; Maria Grazia Monaci; Carmen Spagnuolo; Massimiliano Di Benedetto; Paolo Serravalle; Didier Grandjean (Children, 2023)
(1) Background: Preterm infants spend their first weeks of life in the hospital partially separated from their parents and subjected to frequent potentially painful clinical procedures. Previous research has found that early vocal contact reduces infant pain perception while simultaneously increasing oxytocin (OXT) levels. The current study aims to assess the effect of maternal singing and speaking on mothers. (2) Methods: During a painful procedure over two days, twenty preterm infants were randomly exposed to their mother’s live voice (speaking or singing). Maternal OXT levels were measured twice: before and after singing, as well as before and after speaking. The anxiety and resilience responses of mothers were studied before and after the two-day interventions, regardless of the speaking/singing condition. OXT levels in mothers increased in response to both singing and speech. Concurrently, anxiety levels decreased, but no significant effects on maternal resilience were found. (3) Conclusions: OXT could be identified as a key mechanism for anxiety regulation in parents, even in sensitive care situations, such as when their infant is in pain. Active involvement of parents in the care of their preterm infants can have a positive effect on their anxiety as well as potential benefits to their sensitivity and care abilities through OXT.